Randomized controlled trials: Time for trainees to collaborate on multicenter studies - Gardiner, M; Jain, A (Lippincott, Williams and Wilkins, 2016)
The publications “A Systematic Review of Surgical Randomized Controlled Trials: Part I. Risk of Bias and Outcomes: Common Pitfalls Plastic Surgeons Can Overcome” and “A Systematic Review of Surgical Randomized Controlled Trials: Part 2. Funding Source, Conflict of Interest, and Sample Size in Plastic Surgery” highlight the disappointing quality and quantity of randomized controlled trials in the plastic surgery literature. These issues are well established but resistant to change. We believe that multicenter trainee collaboration and the resulting longer-term change in culture will improve the state of randomized controlled trials in plastic surgery.